The Role of Moral Engagement in the Relationship Between Locus of Control and Intention to Commit Corruption among University Students - Devina Puspa Anggraini; Etik Darul Muslikah; Eben Ezer Nainggolan (Psikologi Prima, 2025)
The increasing tendency of integrity-violating behaviors among university students such as academic dishonesty and the normalization of unethical actions demonstrates the urgency of understanding psychological factors that may foster corrupt intentions from an early stage in higher education. This study aims to analyze the relationship between locus of control and intention to corruption and to examine the mediating role of moral engagement. A total of 350 students from public and private universities in Surabaya participated through a convenience sampling technique. Mediation analysis using linear regression showed that internal locus of control decreases intention to corruption (β = –0.088, p = 0.045), whereas the external dimensions, powerful others and chance, increase it (β = 0.526; β = 0.247; p < 0.001). Internal locus of control increases moral engagement (β = 0.299, p < 0.001), while the two external dimensions reduce it. When moral engagement is included as a mediator, the effect of internal locus of control becomes non-significant, whereas moral engagement consistently shows a strong negative effect on intention to corruption (β = –0.462, p < 0.001). These findings highlight that moral engagement plays a crucial role in preventing corrupt behavioral tendencies among university students.